Sinolethrus, a new subgenus of the genus Lethrus Scopoli, 1777 from China (Coleoptera: Geotrupidae: Lethrinae) and new synonymy of the subgenus Paralethrus Nikolajev, 2003 - Bagaturov, Mikhail F.; Hillert, Oliver (Zootaxa, 2023)
Sinolethrus Bagaturov & Hillert, new subgenus is described as a monotypical subgenus for Lethrus serpentifer Semenov & Medvedev, 1935. The new subgenus is distributed in the north-central part of China. An identification key for the subgenera of the genus Lethrus Scopoli, 1777 is provided, diagnostic characters are illustrated. Furthermore, Lethrus mediocris Fairmaire, 1892 is synonymized with Lethrus (Paralethrus) bituberculatus impressifrons Ballion, 1870, and its lectotype is designated.